A intuição nas práticas decisórias em organizações financeiras - Silva, Maria Elenice Torres (2010)
This study aimed to identify and to analyze how managers of financial institutions recognize the use of intuition in decision-making process. It has also been investigated about whether intuitive knowledge are relevant or not to those managers, based on the assumption that bank managers perceive and use the intuitive dimension of knowledge, beyond the rational dimension of knowledge in their decision-making. It has been developed a research based on decision-making Theory and also on current studies on Intuition field available on published scientific literature. It has been done an academic literature research and also a field research, based on description and explanation, in a qualitative approach. The study collected qualitative data from 31 managers of financial institutions in their workplace. Those managers attended an Evoking Word Test, an interview and also answered to a previously prepared questionnaire with questions based on decision-making and intuition studies as research instruments. The result revealed that there is a relationship between the concept of intuition assumed by those managers and the concept of intuition studies. It has also been revealed that those managers have a clear perception that using intuition is important when it comes to decision-making and they actually appreciate that kind of knowledge. The result of the use of their intuition on decision-making are experience, feeling, hit, risk. It was confirmed that managers of financial institutions take into account their intuition when it comes to decisionmaking and that practice promote the growth of their effectiveness in the workplace.